1996
DOI: 10.2172/434423
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the systems prioritization method as a decision-aiding method for the waste isolation pilot plant

Abstract: THE SPMAPPROACHThe goal of SPM was to provide information about how potential activities-twenty-one scientific investigations, three engineered alternatives, and two waste acceptance criteria-when viewed singly or in combination, codd contribute to a demonstration of compliance with EPA long-term performance requirements for the WIPP disposal system:4 For each activity set (a combination of activities), SPM calculated the probability of demonstrating compliance (PDC) if the activity set was implemented, along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…As described by Boak et al (1996), and as illustrated in the overview to the SNL PA methodology in Figure 9 (see Section 1.2.3), SPM can be outlined in eleven steps:…”
Section: Systems Prioritization Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…As described by Boak et al (1996), and as illustrated in the overview to the SNL PA methodology in Figure 9 (see Section 1.2.3), SPM can be outlined in eleven steps:…”
Section: Systems Prioritization Methodsmentioning
confidence: 99%
“…The analysis indicated that a demonstration of compliance could be anticipated within the DOE WIPP schedule. These eight activities were completed in support of and their outcome reflected in the successful 1996 Compliance Certification Application (Boak, Prindle, et al 1997). …”
Section: Systems Prioritization Methodsmentioning
confidence: 99%
See 2 more Smart Citations